Quantification of Sheet Resistance in Boron‐Diffused Silicon Using Micro‐Photoluminescence Spectroscopy at Room Temperature. Issue 10 (1st September 2017) - Nguyen, Hieu T.; Johnston, Steve; Paduthol, Appu; Harvey, Steven P.; Phang, Sieu Pheng; Samundsett, Christian; Sun, Chang; Yan, Di; Trupke, Thorsten; Al‐Jassim, Mowafak M.; Macdonald, Daniel
Abstract : A micro‐photoluminescence‐based technique is presented, to quantify and map sheet resistances of boron‐diffused layers in silicon solar cell precursors with micron‐scale spatial resolution at room temperature. The technique utilizes bandgap narrowing effects in the heavily‐doped layers, yielding a broader photoluminescence spectrum at the long‐wavelength side compared to the spectrum emitted from lightly doped silicon. By choosing an appropriate spectral range as a metric to assess the doping density, the impacts of photon reabsorption on the analysis can be avoided; thus, an accurate characterization of the sheet resistance can be made. This metric is demonstrated to be better representative of the sheet resistance than the surface doping density or the total dopant concentration of the diffused layer. The technique is applied to quantify sheet resistances of 12‐μm‐wide diffused fingers in interdigitated back‐contact solar cell precursors and large diffused areas. The results are confirmed by both 4‐point probe and time‐of‐flight secondary‐ion mass spectrometry measurements. Finally, the practical limitations associated with extending the proposed technique into an imaging mode are presented and explained. Abstract : A micro‐photoluminescence‐based technique to quantify and map sheet resistances of boron‐diffused layers in silicon solar cell precursors with micron‐scale spatial resolution at room temperature is reported. The technique utilizes bandgap narrowing effects in the heavily‐doped layers, yielding a broader photoluminescence spectrum at the long‐wavelength side compared to the spectrum emitted from lightly‐doped silicon.